The Influence Of Product Quality, Price And Location On Consumer Purchasing Decisions (Survey On Alle'chantre Tasikmalaya Store Consumers) - Denni Mochamad Faisal; Rita Tri Yusnita; Mila Karmila (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study is to determine the influence of product quality, price, and location on consumer purchasing decisions of Alle'Chantre Tasikmalaya outlets. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Alle'Chantre. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that product quality, price, and location have a significant effect both partially and simultaneously on the purchasing decisions of consumers of Alle'Chantre Tasikmalaya outlets.